Nonlinear Effects of Altitude on Child Growth in Peru – A Multilevel Analysis - Marini, Alessandra; Gragnolati, Michele (World Bank, Washington, DC, 2012)
Growth at high altitude has been the object of many investigations after experimental studies on animals showed that hypoxia at high altitude slows growth. Many studies have also looked at the Andean populations and found different results. Even though a few studies find that individuals living at high altitudes are smaller than the ones living at low altitudes, a significant group of studies does not reveal such a clear relationship. This study focuses on Peru, a country characterized by a diverse territory, great altitude variations, and a population with a wide socioeconomic gradient. The analysis differs from previous studies in three ways. First, in an attempt to reconcile the main findings of the biological literature with the economic models of child health, it explores the relationship between altitude and child health within a multivariate framework. Second, it benefits from a large spectrum of altitude data and does not concentrate on one or two isolated villages. Third, it takes into account the cluster nature of the data and controls for correlation of variables in the same cluster through multilevel statistical modeling. After controlling for characteristics of the children, families, and communities, the data show a significant nonlinear relationship between altitude and child nutritional status. Peruvian children living at medium/high altitudes appear to be worse off than children living at extremely high altitudes, where the negative effect of hypoxia on growth could be compensated by other favorable health and environmental conditions.